Programmed cell death evidence in wheat (Triticum aestivum L.) roots induced by aluminum oxide (Al2O3) nanoparticles - VARDAR, FİLİZ (TAYLOR & FRANCIS LTD, 2017)
Nanoparticles have been recognized as an abiotic stress factor in the last decade. Although they are extensively used in nanotechnology, the possible effects of nanoparticles on plants are still unclear. Therefore the aim of the present study was to determine the dose dependent effects of 13 nm-sized aluminum oxide nanoparticles (Al2O3 NPs) on wheat roots correlating with programmed cell death related characteristics. Exposure to different concentrations of Al2O3 NPs (5, 25 and 50 mg ml(-1)) decreased the mitotic indices dose dependently and caused chromosomal abnormalities such as c-mitosis, monopolar metaphase and stickiness after 96h. Loss of plasma membrane integrity and irregular microtubule aggregations were determined. Nuclear deformations and TUNEL positive reactions indicating programmed cell death were also observed. Al2O3 NP-induced caspase 3, 8 and 9-like activities which control programmed cell death were observed in all concentrations. According to our results Al2O3 NPs induced programmed cell death in wheat roots after 96h.
Keywords: Aluminum oxide nanoparticles; caspase-like activities; microtubule; mitotic index; programmed cell death; wheat; CASPASE-LIKE PROTEASES; SILVER NANOPARTICLES; PLANTS; GENOTOXICITY; ACTIVATION; PARADIGM; STRESS